IDENTIFIKASI PARASIT PADA IKAN BETOK (Anabas testudieus) - Junius Akbar (Bioscientiae, 2011)
Research on identification of parasitic organism in climbing perch (Anabas testudineus) was carried out.  The purpose of the research was to identified parasitic organism which infecting climbing perch including parasitic intensity,  prevalency, and coefisien of corelation.  The result showed that several organs such as gills and intestine, infected parasitic organism. The parasitic organism are Nematoda,  Dactylogyrus sp, and Trichodina sp.